Molecular phylogenetic investigations of Triops granarius (Lucas, 1864 (Branchiopoda: Notostraca) from the type locality of the former Apus orientalis Tiwari, 1952 and three other localities in the Western Ghats of India - Modak, Nikhil; Korn, Michael; Padhye, Sameer M. (Zootaxa, 2018)
We investigated the phylogenetic position of Triops granarius populations from four localities in the Western Ghats using partial sequences of three mitochondrial genes (COI, 12S rRNA and 16S rRNA) publicly available on the GenBank database. One of these localities, Panchgani, is particularly important since it is the type locality of the former Apus orientalis which is currently treated as a junior synonym of T. granarius. Phylogenetic analyses reveal that populations from all the four localities (Kolhapur, Chalkewadi, Panchgani, and Dighi) form a single lineage, which is here named ‘Maharashtra lineage’. One of the two previously published samples from India, treated as lineage ‘Triops granarius 4’ is nested within this clade. The ‘Maharashtra lineage’ is separated from other lineages by mean maximum likelihood distance ≥ 11.9% in the COI gene. This distance is suggestive of a separation on species level from other lineages of T. granarius. This interpretation is further supported by a conservative genus-wide species delimitation analysis performed in the present study upon application of the Automatic Barcode Gap Discovery method. The ‘Maharashtra lineage’ branches out in two sub-lineages of Panchgani+Kolhapur and Dighi+L4+Chalkewadi samples, separated by 5.9% mean ML distance (uncorrected p-distance = 5.4%) in COI. The application of a 5% threshold to the COI dataset would thus even suggest a possible differentiation of both sub-lineages on species level. Comparative morphological data is presently not available because most vouchers associated with the sequences were depleted for DNA extraction. Further studies are needed in order to prepare a sound taxonomic revision. Thus, in the current study we refrain from re-instating Apus orientalis to full species status (likewise, for other names of Asian taxa in this morphogroup, including Apus sinensis Uéno, we retain the status as junior synonym of T. granarius). Nonetheless, our study highlights the fact that still there may be undescribed cryptic species associated with the specific name in this part of Western Ghats (Linnean Shortfall) and paves the way for future taxonomic investigations and conservation strategies for the genus Triops in India.